BIOLOGY OF SPERMOLOGUS RUFUS BOHEMAN (COLEOPTERA: CURCULIONIDAE) ADULT PHASE - BARRETO, Marliton Rocha; dos ANJOS, Norivaldo (Scientia Agraria, 2002)
The study was carried out under controlled conditions at the Forest Entomology Laboratory of the Federal University of Viçosa, Minas Gerais. Morphology, survival, longevity and behavior in adult phase of Spermologus rufus Boheman were studied. Adults showed reddish brown colour. The maximum lenght and width of the males were, in average, 8.18+0.37 mm and 3.33+0.14 mm, respectively, and those of the females 8.61+0.43 mm and 3.39+0.13 mm, respectively. Females showed longer and narrower rostrum than males. Sexual proportion was 1.0 female to 1,43 males. Mean longevity was 219+66.9 days for males and 166+53 for females. There was only one egg in 80.45% of the seeds. Seed medial region and the insertion point were preferred for oviposition. Eggs were laid isolated and the mean number of eggs laid for female was 146.7+43.9. Average periods of preoviposition and ovipositon were 11.1+7.5 and 118.1+42.3 days, respectively. Adults survived 56.6 days, on average, without feeding. They showed polivoltinism, thanatosis, negative phototaxis; they did not fly and walked about actively when food became scarce.